2019
DOI: 10.1111/csp2.50
|View full text |Cite
|
Sign up to set email alerts
|

Climate change likely to reshape vegetation in North America's largest protected areas

Abstract: Climate change poses a serious threat to biodiversity and unprecedented challenges to the preservation and protection of natural landscapes. We evaluated how climate change might affect vegetation in 22 of the largest and most iconic protected area (PA) complexes across North America. We use a climate analog model to estimate how dominant vegetation types might shift under mid-(2041-2070) and latecentury (2071-2100) climate according to the RCP 8.5 scenario. Maps depicting vegetation for each PA and time perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 100 publications
(181 reference statements)
0
31
0
Order By: Relevance
“…Landscape-level changes of the habitat mosaics are also slow compared to European and North American areas (cf. Biró et al 2013, 2018, Holsinger et al 2019, Wang et al 2020. The Mongolian landscape is and is perceived as more or less stable.…”
Section: Possible Solutions To Address Adverse Changesmentioning
confidence: 99%
“…Landscape-level changes of the habitat mosaics are also slow compared to European and North American areas (cf. Biró et al 2013, 2018, Holsinger et al 2019, Wang et al 2020. The Mongolian landscape is and is perceived as more or less stable.…”
Section: Possible Solutions To Address Adverse Changesmentioning
confidence: 99%
“…A spatially high-resolution assessment of local climate change impacts inside protected areas worldwide is required to guide local protected area management towards global conservation goals (Felton et al 2009). Loarie and colleagues provide such an assessment, but that is restricted to temperature change (Loarie et al 2009) (Hannah et al 2007, Araújo et al 2004, Velazco et al 2019, Bagchi et al 2013, Barredo et al 2016, Holsinger et al 2019, Langdon and Lawler 2015, Regos et al 2016.…”
Section: Optimising Field Surveys For Efficient Monitoring Of Speciesmentioning
confidence: 99%
“…The predictions show that fire occurrence probability and burned area are expected to increase gradually with climate warming in the 21st century (Tymstra et al, 2007). However, recent studies suggest that although vegetation composition may not change rapidly with climate change in the early 21st century, it will change significantly in the middle and end of 21st century (Holsinger et al, 2019;Jiang et al, 2013). For example, Holsinger et al (2019) reported that deciduous species are expected to begin replacing coniferous species as early as the 2050s.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent studies suggest that although vegetation composition may not change rapidly with climate change in the early 21st century, it will change significantly in the middle and end of 21st century (Holsinger et al, 2019;Jiang et al, 2013). For example, Holsinger et al (2019) reported that deciduous species are expected to begin replacing coniferous species as early as the 2050s. Increasing deciduous species will alter fuel properties and loads, reducing the flammability of boreal forests.…”
Section: Introductionmentioning
confidence: 99%